Assessing validity and reliability of the Transition Shock Scale for Undergraduate Nursing Students (TSS, Chinese version) in associate degree nursing students - Huiting Weng; Ziwei Ding; Li Yang; Bo Zhang; Yuanyuan Luo; Qin Wang (BMC Nursing)
Abstract Background The Transition Shock Scale for Undergraduate Nursing Students assesses transition to undergraduate nursing students. The TSS is a tool used in various countries and has been translated into Chinese; however, associate degree nurses dominate China’s nursing workforce, it needs to be validated in associate degree nursing interns. This study aimed to analyze the TSS (Chinese version) validity and reliability in Chinese associate degree nursing interns. Method This methodological validity study investigated internal consistency and reliability. The critical ratio (CR) method and correlation analysis are used for item screening of the scale. Eight experts in nursing management and nursing education were invited to assess the scale’s content validity. Construct validity was assessed using Pearson’s correlation between domains, exploratory factor analysis, and Confirmatory Factor Analysis. This methodological validity study investigated internal consistency and reliability using Cronbach’s alpha and intraclass correlation coefficients (ICC). The level of significance was set at 5%. Results This study included 800 associate degree nursing interns from 8 Hunan Province, China hospitals. Validity analysis showed positive and significant correlations between all TSS (Chinese version) domains, ranging from 0.344 to 0.772. The internal consistency and reliability of the total TSS (Chinese version) score were high (Cronbach’s alpha = 0.925; intraclass correlation coefficient = 0.908). The content validity assessment showed that the I-CVI ranged from 0.875 to 1.000, and the S-CVI was 0.951. Exploratory factor analysis was performed by orthogonal rotation of the data using principal component analysis and maximum variance, and three common factors with eigenroots greater than 1.0 were extracted, with a cumulative variance contribution of 61.095%. Furthermore, confirmatory factor analysis demonstrated the following values of goodness of fit: RMSEA = 0.062, CFI = 0.953, TLI = 0.939, SRMR = 0.0389, χ2/df = 4.064. Thus, the TSS (Chinese version) discriminant and concurrent validities were confirmed. Conclusion TSS (Chinese version) contains 6 dimensions and 18 items, which has good reliability and validity among associate degree nursing interns, and can be used as an evaluation tool for transition shock in associate degree nursing interns.